Lichen novelties from Corvo Island (Azores, Portugal) - Rodrigues, António Félix (2024)
Background Corvo is a small and remote island in the western group of the Azores Archipelago, Portugal. The Island's lichen biodiversity was largely understudied, with only 17 species documented to date. New information This study reports 68 new records of lichen species on Corvo Island, representing an addition of two classes, eight orders, 18 families and 43 genera. It includes three new records for the Azores: Acrocordia conoidea (Fr.) Körb., Chrysothrix flavovirens Tønsberg and Glaucomaria rupicola (L.) P.F. Cannon (syn. Lecanora rupicola (L.) Zahlbr.). Additionally, it confirms the presence of three species previously reported in the Archipelago without specific locations: Lecidea phaeops Nyl., Peltigera canina (L.) Willd. and Pertusaria ficorum Zahlbr. This wealth of new lichen species records greatly enriches our understanding of biodiversity and sets a solid groundwork for upcoming ecological investigations in the Azores Archipelago.